The directing vision and two display technologies in the Iraqi Child Theater: عباس قاسم كاظم (Al-Academy, 2021)
The current research contains four chapters. The first topic included the methodological framework that included the problem of research and the need for it, and then the importance of the research, and then the aim of the research, its limits and the definition of terms linguistically, conventionally and procedurally. The second chapter (the theoretical framework) contained two topics, the topic The first is titled: The Outward Vision in Child Theater Performances, while the second topic was titled: Presentation Technology in Child Theater, Chapter Four (Research Procedures), which organized the research community and analyzed its sample, and the fourth chapter contained research results, conclusions and recommendations. The proposals, and the research was concluded with a list of sources and references.